2012
DOI: 10.1364/oe.20.001308
|View full text |Cite
|
Sign up to set email alerts
|

Spiral plasmonic nanoantennas as circular polarization transmission filters

Abstract: We present simulation and experimental results for easily fabricated spiral plasmonic antenna analogues providing circular polarization selectivity. One circular polarization state is concentrated and transmitted through a subwavelength aperture, while the opposite circular state is blocked. The spectral bandwidth, efficiency, and extinction ratios are tunable through geometric parameters. Integration of such structures onto a focal plane array in conjunction with linear micropolarizers enables complete Stokes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…It is worth pointing out that the working principle and performance of our LS‐nanoslit is different from the spiral plasmonic antenna and AS , which behaved as a circular polarization transmission filter and as a circular polarization analyzer, respectively. They were designed for a single operational wavelength, where circular polarization transmission filter of had lower ER (compared to our LS‐nanoslit) and circular polarization analyzer of was restricted to the near field. Mathematically our design is based on the algorithm of LS denoted by (r=a.eb.φ), in which the rotation angle φ is an exponential function of r .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is worth pointing out that the working principle and performance of our LS‐nanoslit is different from the spiral plasmonic antenna and AS , which behaved as a circular polarization transmission filter and as a circular polarization analyzer, respectively. They were designed for a single operational wavelength, where circular polarization transmission filter of had lower ER (compared to our LS‐nanoslit) and circular polarization analyzer of was restricted to the near field. Mathematically our design is based on the algorithm of LS denoted by (r=a.eb.φ), in which the rotation angle φ is an exponential function of r .…”
Section: Resultsmentioning
confidence: 97%
“…An ideal approach would be to employ a single planer structure that can differentiate between the transmitted or reflected circular polarizations of opposite handedness. In this regard, Bachman et al reported a spiral plasmonic antenna, which could function as a circular polarization transmission filter. However, it suffered meager performance in terms of extinction ratio (ER) and bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…The excitation of SPPs results in a strong local enhancement of the electromagnetic field at the interface [1], and makes it possible to be focused into a strongly confined spot with size beyond the diffraction limit by appropriately designed plasmonic lens structures. Owing to the subwavelength scale feature and field enhancement effects of SPPs, they have attracted a variety of optical applications, such as probes of the scanning near-field optical microscopy [2], high-density optical data storage [3,4], analyzing circularly polarized lights [5][6][7][8][9], light focusing [10][11][12] and so on. At optical frequencies, planar focusing devices have been demonstrated by using arrays of nanoslits [13,14], nanoholes [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Appropriately designed metallic structures can excite SPs on metallic surface and generate optical vortices, which enable applications in areas such as chiral exciting [2], circular polarizer [3][4][5], optical trapping or rotating [6,7]. Spiral gratings were often used in these structures to effectively excite surface plasmon polaritons (SPPs) and acquire spin dependent properties.…”
Section: Introductionmentioning
confidence: 99%